Premiere Elements 8 : the missing manual - Grover, Chris, 1955- (Missing manual., 2009)
Whether you're aiming for YouTube videos or Hollywood-style epics, you need what Premiere Elements can't provide: crystal-clear guidance and real world know-how. This Missing Manual delivers. Packed with great ideas on how to spiff up your footage, this book helps you avoid the dreaded Help! I Never Do Anything With My Video syndrome. With this book, you'll learn how to use Premiere's two approaches to filmmaking: The quick-and-easy InstantMovie technique, and the classic, handcrafted approach for frame-by-frame editing with fine-tuned transitions, effects, and more. Premiere expert Chris Grover combines a touch of humor with insights, tips, and tricks culled from years of moviemaking experience to help you release your inner Scorsese. Create movies from start to finish with hands-on, step-by-step instructions Use InstantMovie to whip up a video ready for prime time Learn frame-by-frame editing to handcraft your story like the pros do Share your movie by saving it to disc, uploading it, or emailing it Add video effects that dazzle Use keyframes to precisely control cuts, special effects, and sound Tap Premiere's automated tools to analyze, organize, and rate your clips.